Evaluation of caesarean section practices according to Robson’s 10-group classification at a level two maternity ward in Conakry, Guinea - Leno, Daniel W. A.; Bah, Mamoudou E.; Moumbagna, Jerry C.; Millimouno, Tamba M.; Lamah, David; Delamou, Alexandre; Sy, Telly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The frequency of caesarean sections (CS) increased dramatically in the world over the last twenty years. The objective of this study was to evaluate caesarean section practices based on Robson classification in an urban referral hospital in Conakry, Guinea Methods: We conducted a cross-sectional study of 2,266 birthing records collected at the maternity ward of the Coronthie Communal Medical Center in Conakry, from January 1st to December 31st 2016. We included in the study all women who had a caesarean section and whose medical records were complete. Robson’s classification was used to classify women into 10 groups based on maternal and fetal characteristics. The relative size of each group, its gross caesarean section rate as well as its contribution to overall caesarean section rate and the main caesarean section indications were calculated. Results: In 2016, 769 caesarean sections were performed out of 2,266 deliveries, corresponding to a hospital section rate of 33.9%. Groups 5 (11.0%), 1 (4.8%), and 3 (4.3%) of the Robson classification were the most contributors to registered hospital caesarean section rate. The main indications for caesarean section were uterine scar in group 5 and acute fetal distress in groups 1 and 3. Conclusions: The systematic reference to the Robson classification could help to identify and avoid the relative indications of the caesarean section in urban Guinea. Besides, increasing induction of labor and strengthening providers’ capacities in emergency obstetric and newborn care services could contribute to reduce caesarean section rates in Guinea.